Macular thickness measured by spectral-domain optical coherence tomography in healthy Thai eyes - Choovuthayakorn J. (2014)
Purpose: To describe the macular thickness measured by spectral-domain optical coherence tomography (SD-OCT) in healthy eyes of Thai people. Design: Prospective cross-sectional study. Methods: Three hundred sixty-eight healthy participants underwent a comprehensive ophthalmic examination, including Spectralis SD-OCT scanning, at Chiang Mai University Hospital. The images were obtained over maculae, using a high-speed volumetric raster scan pattern with lines 240 μm apart. Information was collected from both eyes of each person, with only the right one being used unless it was found to be ineligible (in which case the left eye was studied). A mean retinal thickness was calculated based on nine areas that corresponded to the Early Treatment Diabetic Retinopathy Study by OCT mapping software. The relationships between retinal thickness and sex, age, axial length, and spherical equivalence were analyzed. Results: The mean age of the subjects was 49.17 ± 17.24 years. The mean central retinal thickness was 259.18 ± 19.08 μm, the mean foveal volume was 0.20 ± 0.02, and the mean total macular volume was 8.59 ± 0.37 mm 3. Central subfield (CSF) thickness and foveal volume were significantly greater in men than in women (both P < 0.001). When analyzed for six age groups by ANOVA, the CSF thickness showed no significant difference among the groups, with a P value of 0.280, and foveal volume showed no significant difference among the six groups, with a P value of 0.341. After age adjustment, axial length was correlated positively with the CSF thickness (P < 0.001, Pearson correlation). Conclusions: The normal macular thickness in Thais is thinner than those reported for other populations when measured using the Spectralis SD-OCT. Male gender and axial length were correlated positively with CSF thickness. © 2012 Japanese Ophthalmological Society.